2001
DOI: 10.1073/pnas.011370498
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for ATP-sensitive potassium channel diversity: Functional coassembly of two pore-forming subunits

Abstract: ATP-sensitive potassium channels are an octomeric complex of four pore-forming subunits of the Kir 6.0 family and four sulfonylurea receptors. The Kir 6.0 family consists of two known members, Kir 6.1 and Kir 6.2, with distinct functional properties. The tetrameric structure of the pore-forming domain leads to the possibility that mixed heteromultimers may form. In this study, we examine this by using biochemical and electrophysiological techniques after heterologous expression of these subunits in HEK293 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 12 publications
6
77
0
Order By: Relevance
“…HEK-293 cells were transfected with Kir2.1 and Kir2.4 subcloned into in pcDNA3 vectors (Invitrogen) using LipofectAMINE (Life Technologies, Inc) according to the manufacturer's instructions (Cui et al, 2001). Stable cell lines were established using the appropriate antibiotic selection (G418, for Kir2.1; Zeocin for Kir2.4) as detailed previously (Giblin et al, 1999).…”
Section: Transfection and Generation Of Monclonal Stable Linesmentioning
confidence: 99%
“…HEK-293 cells were transfected with Kir2.1 and Kir2.4 subcloned into in pcDNA3 vectors (Invitrogen) using LipofectAMINE (Life Technologies, Inc) according to the manufacturer's instructions (Cui et al, 2001). Stable cell lines were established using the appropriate antibiotic selection (G418, for Kir2.1; Zeocin for Kir2.4) as detailed previously (Giblin et al, 1999).…”
Section: Transfection and Generation Of Monclonal Stable Linesmentioning
confidence: 99%
“…The channel conductance of this K ATP channel is intermediate between those of Kir6.1 and Kir6.2 (Babenko et al, 1998). In functional expression experiments, Cui et al (2001) have recently reported that heteromultimerization readily occurs between Kir6.1 and Kir6.2, producing functional glibenclamide-sensitive K ATP channels. Cui et al (2001) also suggest a possibility that K ATP channels in pig urethra may possess a heteromeric Kir6.1/ Kir6.2 structure.…”
Section: T Yunoki Et Almentioning
confidence: 99%
“…In functional expression experiments, Cui et al (2001) have recently reported that heteromultimerization readily occurs between Kir6.1 and Kir6.2, producing functional glibenclamide-sensitive K ATP channels. Cui et al (2001) also suggest a possibility that K ATP channels in pig urethra may possess a heteromeric Kir6.1/ Kir6.2 structure. Further study is certainly necessary in order to elucidate the interaction of Kir subunits in pig urethral K ATP channels.…”
Section: T Yunoki Et Almentioning
confidence: 99%
“…Kir6.1 and Kir6.2, being 64% identical, display overlapping tissue expressions and form heteromeric complexes when coexpressed (Babenko et al, 2000;Cui et al, 2001;Pountney et al, 2001;van Bever et al, 2004). On the contrary, based on the study from Giblin et al, it is generally accepted that SUR1 cannot coassemble with SUR2 to form K ATP channels (Giblin et al, 2002;Babenko, 2005;Neagoe and Schwappach, 2005;Tricarico et al, 2006), even though SUR1 and SUR2 share ‫%56ف‬ identity and are coexpressed in many cell types (Baron et al, 1999;Liss et al, 1999;Shi et al, 2005;Tricarico et al, 2006).…”
Section: Introductionmentioning
confidence: 99%